Chemical profiles of three varieties of germinated rice based on LC-MS and their antioxidant activity - Pramai, Phaiwan; Thongsook, Tipawan; Thanasukarn, Parita; Jannoey, Panatda; Nuengchamnong, Nitra; Chen, Feng; Maulidiani, Maulidiani; Abas, Faridah; Jiamyungyuen, Sudarat (Food and Applied Bioscience Journal, 2019)
In this study, chemical profiles in different germinated rice extracts (GREs) using different solvent extraction ratio were investigated. Three varieties of germinated rice (GR), including germinated white rice (GWR), germinated black rice (GBR) and germinated red rice (GRR) were extracted using 70 and 100% ethanol (v/v). Both extracts were characterized for their chemical profiles using liquid chromatography-electrospray ionization. This enzyme is thus the target of the widely available cholesterol-lowering drugs known collectively as the statins (Chen et al., 2011). This type of medication is usually an option for expression of LDL receptors in the liver, which in turn increases the catabolism of plasma LDL and lowers the plasma concentration of cholesterol, which is considered, by those who accept the standard lipid hypothesis, an important determinant of atherosclerosis. Coronary Heart Disease (CHD) treatment. Lovastatin has been well known as a strong HMG-CoA reductase quadrupole-time-of-flight mass spectrometry (LC-ESI-Q-TOF-MS). The content of γ-aminobutyric acid (GABA), total phenolic content (TPC), and antioxidant activities were also determined. The chemical profiles of GREs are composed of organic acids, amino acids, vitamins, flavonoids, and phenolic compounds.